Universal Mobility-Field Curves For Electrons In Polysilicon Inversion Layer - Muhammad Idzdihar , Idris; Faiz , Arith; Siti Amaniah , Mohd Chachuli; Haziezol Helmi, M. Yusof (IJENS, 2013)
This paper reports the studies on the inversion-layer mobility in n-channel Poly-Si TFT’s with 1016cm-3 substrate impurity concentration. The validity and limitations of the universal relationship between the inversion layer mobility and the effective normal field (Eeff) was examined.